Pengaruh Profitabilitas, Investment Opportunity Set dan Risiko Audit terhadap Audit Report Lag pada Perusahaan Perbankan - Rukmana Koja; Nelvirita Nelvirita (Universitas Negeri Padang, 2026)
This study investigates the effect of profitability, Investment Opportunity Set (IOS), and audit risk on Audit Report Lag (ARL) among banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sample includes 39 banks, yielding a total of 117 observations. Secondary data were extracted from audited financial statements. ARL was measured as the number of days from the fiscal year-end to the auditor’s report issuance. Profitability was proxied by Return on Assets (ROA), IOS by the market-to-book value of equity (MVEBVE) ratio, and audit risk using trend-percentage analysis of revenues and expenses. Analysis was conducted using panel data regression, employing the Random Effects Model. Results show that individually, profitability (p = 0.1048), IOS (p = 0.5280), and audit risk (p = 0.2876) do not have a statistically significant effect on ARL. Simultaneously, the three variables also do not significantly affect ARL (Prob(F) = 0.1852), with an R² of 0.016, indicating that the model explains only a minimal portion of ARL variance. These findings suggest the need to consider other determinants, such as audit complexity, board governance quality, audit firm size, or regulatory factors in reducing audit report delays in the banking sector.